O aluno indígena e a educação especial: um estudo do contexto amazônico - Martins, Jaqueline da Silva (Brasil, 2020)
This paper addresses the theme of special education and indigenous education. The research aimed to map the number of indigenous students with disabilities enrolled in schools in the state of Amazonas between 2007 and 2017 and the type of care that indigenous children in the municipality of Humaitá - AM receive. The guiding question came from the following problem: what are the shortcomings of indigenous children enrolled in village schools and how are they addressed? To elucidate our objectives we are guided by the qualitative approach of the case study research. For data construction, we conducted a bibliographic research and data analysis of the National Institute of Educational Studies and Research Anísio Teixeira (INEP) as well as interviewing the coordinator of indigenous school education of the Municipal Secretariat of Education to analyze the care for people with disabilities in indigenous villages of the municipality of Humaitá. The research in question was based on current legislation and various studies Jannuzzi (1992) Mazzotta (2005) Ferreira (2001) Sá (2014) among others. The investigation revealed that the interface between indigenous education and special education in legislation is recent in Brazil and that there has been a significant growth in the number of indigenous students with disabilities enrolled in indigenous schools in the state of Amazonas. However with regard to specialized care is still precarious.